2012
DOI: 10.1016/j.ajog.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial microparticles and the antiangiogenic state in preeclampsia and the postpartum period

Abstract: OBJECTIVE(S) To determine if endothelial microparticles (EMPs), markers of endothelial damage, are associated with soluble fms-like tyrosine kinase 1 (sFlt1), soluble endoglin (sEnd), and placental growth factor (PlGF) in women with preeclampsia. STUDY DESIGN: A prospective cohort study was conducted on 20 preeclamptic women and 20 controls. EMP’s measured by flow cytometry, sFlt1, sEnd, and PlGF were measured at time of enrollment, 48 hours, and 1 week postpartum. RESULTS Preeclamptic CD31+/42−, CD 62E+, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 22 publications
2
52
0
2
Order By: Relevance
“…6 The number of erythrocyte and endothelial MVs increases in severe PET, 7 and shedding of trophoblast MVs into maternal circulation is higher in early-onset than late-onset diseases. 8 It is of interest that MVs of women with PET were found to promote vascular wall inflammation.…”
Section: Hypertensionmentioning
confidence: 99%
“…6 The number of erythrocyte and endothelial MVs increases in severe PET, 7 and shedding of trophoblast MVs into maternal circulation is higher in early-onset than late-onset diseases. 8 It is of interest that MVs of women with PET were found to promote vascular wall inflammation.…”
Section: Hypertensionmentioning
confidence: 99%
“…A defect of deep placentation [9][10][11][12][13] is proposed to generate utero-placental ischemia [14][15][16], placental endoplasmic reticulum and oxidative stress [17][18][19][20][21][22], and subsequently systemic intravascular inflammation [23][24][25] and endothelial dysfunction [17,[26][27][28][29][30][31][32][33][34]. The circulating concentrations of pro-inflammatory cytokines, such as interleukin (IL)-1-b and tumor necrosis factor (TNF)-a [35][36][37][38][39], as well as other inflammatory mediators (such as IL-6) [36,[40][41][42] are typically elevated in patients with preeclampsia, although this is not a universal feature [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, EVs are often found in circulating blood, and the number of EVs is elevated in response to acute and chronic inflammation associating with common diseases such as stroke, myocardial infarction, Kawasaki disease, sepsis, preeclampsia, atherosclerosis, diabetes mellitus, and metabolic syndrome Boulanger et al, 2006;Ding et al, 2014;Koga et al, 2005;Mostefai et al, 2008;Petrozella et al, 2012;Simak et al, 2006;Tan et al, 2013). Nonetheless, EVs are produced by many types of cells in response to inflammation, vascular endothelial cells are thought to be one of the major cell types that release EVs into the bloodstream (Martinez et al, 2005).…”
Section: Common Diseases Related To Inflammationmentioning
confidence: 99%
“…Clinically, the number of EVs has been observed to increase in the bloodstream of patients suffering from acute and chronic inflammation evoked by diseases such as sepsis, stroke, preeclampsia, atherosclerosis, diabetes mellitus, metabolic syndrome, and cancer Boulanger et al, 2006;Koga et al, 2005;Mostefai et al, 2008;Petrozella et al, 2012;Simak et al, 2006). Several studies have reported that EVs mediate intercellular communica-tions by releasing encapsulated materials such as messenger RNAs (mRNAs), microRNAs (miRNAs), and proteins, to target cells (Al-Nedawi et al, 2009Fujita et al, 2014;Kawamoto et al, 2012;Tominaga et al, 2015;Waldenstrom et al, 2012;Yamamoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%